Investigation of the Mozart sonata effect on contextual memory extinction - Rodolfo Souza de Faria; Amanda Di Gesu; Lelis do Vale Miranda; Luciano Magalhães Vitorino; Clarissa Maria Ferreira Trzesniak; Cesar Renato Sartori (Einstein (São Paulo))
ABSTRACT Objective This study aimed to analyze the influence of Mozart’s Sonata K.448 on contextual memory extinction in male mice. Methods Male mice were divided into three groups (G1-Mozart, G2-Ambience, G3-Control). Throughout the project, only the first group was exposed to the sonata at the intrauterine stage. Only Groups 1 and 2 underwent aversive training; subsequently, all groups participated in extinction and recall tests. Results On the first day of extinction, G1’s freezing time was longer than G2’s and G3’s, whilst on the second day it was only longer than G3’s. Finally, on the fifth day, G1’s freezing time was shorter than that of G2. During the second and third days of extinction, G1’s freezing time decreased more than G3’s, whereas during the fourth and fifth day, G1 upheld its freezing time, whereas G2’s extended. During recall, G1 had a longer freezing time than G3. All results were statistically significant (p≤0.05). Conclusion Based on the results, we concluded that male mice exposed to Mozart’s Sonata K.448 showed increased freezing time, suggesting an impact of the music on memory formation. However, they exhibited a linear extinction memory process. This progressive decrease in freezing behavior was not observed in the ambient and Control Groups.